Two new species of the family Tetrablemmidae (Araneae) from Laos and Malaysia - Lin, Yucheng; Li, Shuqiang; Jäger, Peter (Zootaxa, 2012)
Two new species of the spider family Tetrablemmidae are described: Brignoliella besutensis sp. nov. from Malaysia and Tetrablemma namkhan sp. nov. from Laos. The family Tetrablemmidae is reported from Laos for the first time.